Discussion of the problem of functional constipation and irritable bowel syndrome in the reports of the International Congress on Neurogastroenterology and Motility (Bologna, 2012) - A. A. Sheptulin; M. A. Vize-Khripunova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of the Review. To characterize the main points of the reports devoted to the functional gastrointestinal disorders presented at the International Congress on Neurogastroenterology and Motility (Bologna, 2012).Key points. Functional constipation is widely spread in the population. The mechanisms of cardiotoxic effect of cisapride and tegaserod were demonstrated and the safety of the administration of prucalopride was assessed. Currently the new pathogenic mechanisms of the irritable bowel syndrome (IBS) are under active study: the role of the infection, the violation of the intestinal mucosa permeability, the immune shifts, the reduction in the bile acids resorption etc.Conclusion. IBS is not considered as purely functional disease, it is recognized as multifactorial disease.